2012
DOI: 10.1016/j.outlook.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Altruism in clinical research: Coordinators’ orientation to their professional roles

Abstract: Background Research coordinators have significant responsibilities in clinical trials that often require them to find unique ways to manage their jobs, thus re-shaping their professional identities. Purpose The purpose of this study is to identify how research coordinators manage role and ethical conflicts within clinical research trials. Method A qualitative study combining observation and 63 semi-structured interviews at 25 research organizations was used. Discussion Altruism is a recurring theme in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Professionals who consent patients for participation in research have reported ethical challenges because of role conflicts. For example, research coordinators must balance their roles as patient advocates vs. study advocates, and there are situations where these roles conflict (Davis et al 2002;Fisher and Kalbaugh 2012). The challenges of balancing these roles may be particularly pronounced for health professionals, such as genetic counselors, who obtain consent for research as well as provide clinical care (Markel and Yashar 2004), sometimes for the same person.…”
Section: Introductionmentioning
confidence: 99%
“…Professionals who consent patients for participation in research have reported ethical challenges because of role conflicts. For example, research coordinators must balance their roles as patient advocates vs. study advocates, and there are situations where these roles conflict (Davis et al 2002;Fisher and Kalbaugh 2012). The challenges of balancing these roles may be particularly pronounced for health professionals, such as genetic counselors, who obtain consent for research as well as provide clinical care (Markel and Yashar 2004), sometimes for the same person.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of using respected, senior clinicians to improve the uptake of an intervention like ACP is highlighted in the literature. 69,70 Lower effect sizes for patient satisfaction with end-oflife care were found in the study by Brumley et al 52 While the intervention slightly improved outcomes, the authors thought that a major cause for the low effect size was the high mortality rate of the study population before follow-up. Their results suggested that providing a multidisciplinary team early in the disease trajectory of the patient had a small but positive effect on patient satisfaction with end-of-life care.…”
Section: Characteristics Of Acp Interventionsmentioning
confidence: 93%
“…However, altruism was identified as part of the identity of research coordinators, and this is relevant to make volunteers aware of the importance of their participation in clinical research; to minimize conflicts between research and care and to disprove the undervaluing of the coordinator's role (11) . Limitations of the nurse in clinical research were partially overcome by recommendations and incentives of the advisor, so the apprentice could have a distinguished perspective vision in relation to other staff members, that is, the nurse's perspective and how they could significantly contribute to the research.…”
Section: Participation Of Nurses In the Execution Of Clinical Researcmentioning
confidence: 99%